Maraval Road, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of Maraval Road with overhanging trees and grasses - bamboo.
Colour: Black and white; Style: Landscape; Other: Bordered
Keywords: Trinidad and Tobago; Postcards; Roads--Trinidad and Tobago; Bamboo--Trinidad and Tobago; Rural roads--Trinidad and Tobago